"Do you think adolescents' food intake is satisfactory?" – Views of Indian parents and teachers. (1st October 2020) - Rathi, Neha; Riddell, Lynn; Worsley, Anthony
Abstract: Adolescents develop food habits that affect both their present and future health. Underpinned by the stakeholder theory, this study was designed to explore the perspective of parents and nutrition educators regarding urban Indian adolescents' food habits. Thirty-two educators and 280 parents from five independent, English-speaking, secondary schools in Kolkata, India completed a paper-based instrument consisting of both closed and open-ended measures. Qualitative data were subjected to thematic analysis informed by the Template Analysis Technique. Descriptive and cross-tabulation analyses were employed to assess quantitative data. Three quarters (75%) of the respondents were dissatisfied with the ubiquitous consumption of energy-dense, nutrient-poor foods and sugar-sweetened beverages as well as the low intakes of healthy foods like fruits and vegetables among urban Indian adolescents. Six reasons were advanced for such unhealthy consumption including i) Proliferation of fast food retail outlets; ii) Hyper-palatability of fast food; iii) Marketing of fast food on electronic and social media; iv) Diminished household cooking practices; v) Lack of food knowledge; vi) Tendency to seek peer group acceptance. Both parents and educators suggested some healthy eating strategies aimed at improving the food and nutrition situation in Indian secondary schools to foster healthy eating among pupils. These included: i) Restrictions on the sale of unhealthy foods in school canteens; ii) Increased availability of attractive and palatable nutritious foods; iii) Discussion of the advantages of consuming healthy foods and inclusion of food preparation techniques in the school curriculum; iv) Home Economics coursework to be made mandatory for students. The findings suggest that Indian parents and teachers are likely to support changes to the food and nutrition curricula and to school food provision to foster healthy eating among adolescents.